2018
DOI: 10.3390/beverages4030067
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability of Novel Functional Drinks Based on Ricotta Cheese Whey and Fruit Juices

Abstract: To study the storage stability of drinks produced by blending ricotta cheese whey (RCW) with fruit juices, apple-RCW and apple and blueberry mix (50:50)-RCW (juice/RCW ratio: 70/30, 14.5% soluble solids content) were prepared. Color, sugar and organic acid profiles, antioxidant composition, and sensory features were analyzed after 15 to 150 days of storage on an open shelf at room temperature. A browning phenomenon occurred in the apple-RCW-based drink, while no significant color changes occurred in the mix-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Moreover, according to Roland et al (1999), L* values and lipid content have a positive correlation in ice creams. Dairy wheys have reduced lipid and casein contents compared with WM (Morin et al, 2006;Bald et al, 2014;Cortellino and Rizzolo, 2018). However, considering the obtaining process of the evaluated dairy wheys, BUW is the closest to milk in relation lipid and casein contents (Morin et al, 2006), which corroborates with our data of proximate composition and explains the minor color changes by BUW addition.…”
Section: Instrumental Colorsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, according to Roland et al (1999), L* values and lipid content have a positive correlation in ice creams. Dairy wheys have reduced lipid and casein contents compared with WM (Morin et al, 2006;Bald et al, 2014;Cortellino and Rizzolo, 2018). However, considering the obtaining process of the evaluated dairy wheys, BUW is the closest to milk in relation lipid and casein contents (Morin et al, 2006), which corroborates with our data of proximate composition and explains the minor color changes by BUW addition.…”
Section: Instrumental Colorsupporting
confidence: 88%
“…Dairy wheys from the processing of cheeses, ricotta, and butter have bioactive substances for human health, are low fat, and have good functional and technological properties, representing a low-cost raw material for milk replacement in traditional dairy products (Morin et al, 2006;Bald et al, 2014;Cortellino and Rizzolo, 2018). Several studies have evaluated milk replacement by whole cheese whey (CW; Sakhale et al, 2012;Castro et al, 2013), ricotta whey (RW; Gerhardt et al, 2013;Cortellino and Rizzolo, 2018), and butter whey (BUW; Hickey et al, 2018) in several dairy products. However, there are no reports regarding RW and BUW used as milk replacers in ice cream.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The white color of milk results from the presence of colloidal particles, such as milk fat globules and casein micelles, capable of scattering light in the visible spectrum (García-Pérez et al, 2005), which explains the high L* value of the milk ice cream in comparison to that of cheese whey and ricotta whey ice creams. Additionally, considering the obtaining process of the evaluated dairy wheys, butter whey is the closest to milk in relation to lipid and casein contents, yet cheese whey and ricotta whey have reduced lipid and casein contents compared to whole milk (Morin et al, 2006;Bald et al, 2014;Qiu et al, 2015;Cortellino & Rizzolo, 2018). Roland et al (1999) also found that ice cream lightness values increased as fat content also increased when analyzing the effects of fat content on ice cream properties.…”
Section: Instrumental Colormentioning
confidence: 96%
“…Among the alternatives that minimize environmental impact considering nutritional and technological potentials, dairy effluents can have a positive impact not only on consumers' health, but also on cost savings. One of these benefits is the low cost of raw materials, which reduces production costs when there is partial or total replacement of the quantities of milk, eggs, fats, sugar, and even protein from the formulations of several processed dairy products, as shown by several studies (Sakhale et al, 2012;Castro et al, 2013;Gerhardt et al, 2013;Božanić et al, 2014;Cortellino & Rizzolo, 2018;Hickey et al, 2018).…”
Section: Introductionmentioning
confidence: 99%